Prevalence of Medicolegal Cases During Covid-19 Pandemic Lockdown; A Local Experience : Medicolegal Cases During Covid-19 - Murad, Tasneem; Ahmad, Sajjad; Ramzan, Riffat; Ali, Filza; Masood, Riffat; Sana, Sanaila Gull (Pakistan Journal of Health Sciences, 2025)
Medical examinations are essential in legal cases, providing critical evidence that influences judicial outcomes. The COVID-19 pandemic impacted various societal aspects, including the nature and frequency of medical examinations. Objective: To compare the prevalence and types of medicolegal cases reported at District Headquarters Hospital, Rawalpindi, during the pre-pandemic and pandemic periods. Methods: A retrospective comparative cross-sectional study was conducted using data from March 2019 to August 2019 (pre-pandemic) and March 2020 to August 2020 (pandemic). Demographic details, including age and gender, as well as the types of cases (e.g., physical assault, sexual assault, trauma), were analyzed using SPSS version 24.0. Results: The total number of cases increased significantly from 389 in the pre-pandemic period to 441 during the pandemic (P < 0.01). During the pandemic, physical assault cases increased from 122 (31.36%) to 151 (34.24%), and sexual assault cases rose from 39 (10.02%) to 54 (12.24%) (P = 0.013). Blunt trauma cases increased from 79 (20.31%) to 101 (22.9%) and sharp trauma cases from 67 (17.22%) to 89 (20.18%). However, cases involving road traffic accidents (RTA) decreased significantly from 41 (10.54%) to 16 (3.63%) (P = 0.04). Poisoning incidents saw slight changes and the occurrence of burns, particularly chemical burns, increased from 3 (0.77%) to 5 (1.13). Conclusions: The COVID-19 pandemic lockdown has had a profound impact on the prevalence and nature of medicolegal cases. These findings emphasized the need for targeted interventions to address the specific medicolegal challenges exacerbated by pandemic conditions and to support vulnerable populations, particularly in urban areas and among women.